The Medusa reader - Garber, Marjorie B.; Vickers, Nancy J. (New York : Routledge, 2003)
Fascinating and terrifying, the Medusa story has long been a powerful signifier in culture with poets, feminists, anthropologists, psychoanalysts, political theorists, artists, writers, and others. Bringing together the essential passages and commentary about Medusa, The Medusa Reader traces her through the ages, from classical times through the Renaissance to the pop culture, art, and fashion of today. This collection, with a critical introduction and striking illustrations, is the first major anthology of primary material and critical commentary on this most provocative and enigmatic of figures.
Includes bibliographical references (p. [279]-301).
boek